Strengthening the Concept of Data Presentation Through Scratch Media for Grade VII Students - Sudihartinih, Eyus; Ghaida, Silmi; Putri, Hayati Ramadhani; Muzakki, Azmi; Gunawan, Sanie Rachma Setia; Jesse, Efraim; Aqilah, Hafizah; Nisa, Rachmawati Khaerun; Ghefira, Aisyah Muthia (Society : Jurnal Pengabdian Masyarakat, 2026)
AbstractMathematical conceptual understanding is one of the essential foundational competencies in mathematics learning, as it plays a crucial role in understanding more advanced materials. However, in reality, students’ conceptual understanding is still below expectations. To address this issue, this research aims to determine the effect of using the Problem-Based Learning (PBL) model assisted by Scratch media on junior high school students’ conceptual understanding of data presentation material. This research employed a quasi-experimental method with a one-group pretest-posttest design. The sample consisted of 27 seventh-grade students from a public junior high school in Bandung, selected through purposive sampling. The instruments used included essay tests and student satisfaction questionnaires. The results showed a significant increase in posttest scores compared to pretest scores, with the average rising from 56.59 to 82.37. The Wilcoxon test showed a significance value of < 0.001, indicating a statistically significant effect. Additionally, students provided positive feedback on the use of Scratch media, particularly in terms of visual appeal, language clarity, and increased motivation for learning. Therefore, the integration of the PBL model and Scratch has proven effective in enhancing students’ conceptual understanding and providing meaningful learning experiences.AbstrakKemampuan pemahaman konsep matematis merupakan salah satu kompetensi dasar yang penting dalam pembelajaran matematika karena menjadi dasar yang sangat penting untuk memahami materi-materi selanjutnya. Namun realitanya menunjukkan bahwa kemampuan pemahaman konsep matematis masih belum sesuai harapan. Untuk mengatasi permasalahan tersebut, penelitian ini bertujuan untuk mengetahui pengaruh penggunaan model pembelajaran Problem-Based Learning (PBL) berbantuan media Scratch terhadap kemampuan pemahaman konsep matematis siswa SMP pada materi penyajian data. Penelitian ini menggunakan metode quasi eksperimen dengan desain one-group pretest-posttest. Sampel penelitian ini adalah 27 siswa kelas VII di salah satu SMP Negeri di Kota Bandung yang dipilih menggunakan purposive sampling. Instrumen yang digunakan meliputi tes uraian dan angket kepuasan siswa. Hasil penelitian menunjukkan adanya peningkatan signifikan pada nilai postes dibandingkan pretes, dari rata-rata 56,59 menjadi 82,37. Uji Wilcoxon menunjukkan nilai signifikansi < 0,001 yang mengindikasikan adanya pengaruh yang signifikan. Selain itu, siswa memberikan respon positif terhadap media Scratch, terutama dari segi tampilan visual, kemudahan bahasa, serta peningkatan motivasi belajar. Dengan demikian, integrasi model PBL dan Scratch terbukti efektif dalam meningkatkan pemahaman konsep dan pengalaman belajar yang bermakna bagi siswa.Mathematical conceptual understanding is one of the essential foundational competencies in mathematics learning, as it plays a crucial role in understanding more advanced materials. However, in reality, students’ conceptual understanding is still below expectations. To address this issue, this research aims to determine the effect of using the Problem-Based Learning (PBL) model assisted by Scratch media on junior high school students’ conceptual understanding of data presentation material. This research employed a quasi-experimental method with a one-group pretest-posttest design. The sample consisted of 27 seventh-grade students from a public junior high school in Bandung, selected through purposive sampling. The instruments used included essay tests and student satisfaction questionnaires. The results showed a significant increase in posttest scores compared to pretest scores, with the average rising from 56.59 to 82.37. The Wilcoxon test showed a significance value of < 0.001, indicating a statistically significant effect. Additionally, students provided positive feedback on the use of Scratch media, particularly in terms of visual appeal, language clarity, and increased motivation for learning. Therefore, the integration of the PBL model and Scratch has proven effective in enhancing students’ conceptual understanding and providing meaningful learning experiences. Kemampuan pemahaman konsep matematis merupakan salah satu kompetensi dasar yang penting dalam pembelajaran matematika karena menjadi dasar yang sangat penting untuk memahami materi-materi selanjutnya. Namun realitanya menunjukkan bahwa kemampuan pemahaman konsep matematis masih belum sesuai harapan. Untuk mengatasi permasalahan tersebut, penelitian ini bertujuan untuk mengetahui pengaruh penggunaan model pembelajaran Problem-Based Learning (PBL) berbantuan media Scratch terhadap kemampuan pemahaman konsep matematis siswa SMP pada materi penyajian data. Penelitian ini menggunakan metode quasi eksperimen dengan desain one-group pretest-posttest. Sampel penelitian ini adalah 27 siswa kelas VII di salah satu SMP Negeri di Kota Bandung yang dipilih menggunakan purposive sampling. Instrumen yang digunakan meliputi tes uraian dan angket kepuasan siswa. Hasil penelitian menunjukkan adanya peningkatan signifikan pada nilai postes dibandingkan pretes, dari rata-rata 56,59 menjadi 82,37. Uji Wilcoxon menunjukkan nilai signifikansi < 0,001 yang mengindikasikan adanya pengaruh yang signifikan. Selain itu, siswa memberikan respon positif terhadap media Scratch, terutama dari segi tampilan visual, kemudahan bahasa, serta peningkatan motivasi belajar. Dengan demikian, integrasi model PBL dan Scratch terbukti efektif dalam meningkatkan pemahaman konsep dan pengalaman belajar yang bermakna bagi siswa.